ئاستی ڕەچاوکردنی ئیتیکی ڕۆژنامەوانیی میدیای نوێ لە هەرێمی کوردستان (توێژینەوەی هەڵێنجراو) - احمد, پاڤێ جمیل; عبدللە, ئیمان لقمان (Sulaimani Journal for Humanities, 2023)
Abstract: This paper aims at determining the level of observance of ethical standards and principles of the media profession in different online media agencies in the Kurdistan Region of Iraq (KRI). The study, by describing the situation and explaining the ethical standards and principles, followed quantitative methods, through using a designed questionnaire, to proceed with collecting, classifying, and analyzing the data. The research community consists of 157 participants, including; media experts, university lecturers in the departments of media and communication, as well as, academic journalists (who have graduated from media departments, and currently work in a media agency in KRI). Finally, the collected data was analyzed through (SPSS) and results were extracted. Based on the analyzed data, the researchers have found that new media tools in different proportions, social networks, and websites are widely used by the participants of the study, and according to the findings of the study, the practice of ethical standards and principles in the new media outlets in KRI is “unsatisfied”, and almost the principals are disregarded and ignored in media agencies, furthermore, the features and characteristics of new media have great impact in the level of observance of ethical standards and principles in media agencies, in the priority, they follow feature of “speed publication”, which force journalists to involve with more ethical mistakes.
Keywords: Ethics; Digital Media; New Media; Kurdistan Region of Iraq (KRI)